2018
DOI: 10.1016/j.engstruct.2018.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Simplified structural design and LCA of reinforced concrete beams strengthening techniques

Abstract: This work provides the Life Cycle Assessment (LCA) of four commonly used strengthening techniques of reinforced concrete beams. Firstly, it provides a simplified methodology to size the strengthening, overcoming the need of extensive knowledge in structures. Secondly, it provides the application of LCA to the selected techniques. The method improves the applicability of LCA to buildings, analyzes the environmental differences between techniques, and reveals the importance of the anchoring method as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…This trend also applies in the remaining impact indicators (see Appendix A2). Previous literature on RC structures also reported on similar patterns (e.g., [32,37,38,39,40,41]). In this sense, in cases with L = 8.0 m the maximum impacts of reinforcing steel have a larger contribution to the total environmental impacts of the beam, representing up to 50-90 % of the life cycle impacts.…”
Section: Resultssupporting
confidence: 55%
“…This trend also applies in the remaining impact indicators (see Appendix A2). Previous literature on RC structures also reported on similar patterns (e.g., [32,37,38,39,40,41]). In this sense, in cases with L = 8.0 m the maximum impacts of reinforcing steel have a larger contribution to the total environmental impacts of the beam, representing up to 50-90 % of the life cycle impacts.…”
Section: Resultssupporting
confidence: 55%
“…This paper reveals the importance of the lifespan to get economic and environmental benefits and render cost-effectiveness in the long term to the building sector. In the case of the existing buildings an important objective should be to extend their lifespan by means of improving their structure, as suggested in [3]. In the case of new buildings, the objective should be to ensure their potential durability by changing current human tendencies of early substitution.…”
Section: Discussionmentioning
confidence: 99%
“…One question recently posed in the field of buildings LCA is whether or not it is more sustainable to refurbish than to rebuild [3]. Most of the literature on LCA focuses on new construction [4][5][6][7][8], whereas refurbishment is dealt with at a lower extent [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The energy demand for cooling and heating buildings is increasing greatly, especially in developing countries [1]. According to existing literatures, buildings can contribute to up to 40% of the whole energy consumption of our society [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…The energy demand for cooling and heating buildings is increasing greatly, especially in developing countries [1]. According to existing literatures, buildings can contribute to up to 40% of the whole energy consumption of our society [1][2]. Many studies have shown that promoting thermal performance of building envelopes, especially external walls, can significantly decrease buildings' energy demand [3][4][5].…”
Section: Introductionmentioning
confidence: 99%